Systemic treatments for hepatocellular carcinoma: challenges and future perspectives - Francesco Tovoli; Giulia Negrini; Francesca Benevento; Chiara Faggiano; Elisabetta Goio; Alessandro Granito (Hepatic Oncology)
Sorafenib has been the only approved systemic treatment of hepatocellular carcinoma (HCC) for almost a decade. Recently, two new drugs showed positive results in two Phase III studies. The RESORCE trial identified regorafenib as a valid second-line treatment for patients progressing to sorafenib, the REFLECT trial showed that lenvatinib is noninferior to sorafenib as front-line treatment. Following these trials, the therapeutic scenario will be dominated by anti-VEGFR drugs, with three different molecules showing a proven anticancer activity. Some open problems still remain and different immunotherapy trials are underway, following promising preliminary results. In this review we analyze: the most recent advancements about patients treated with sorafenib; the results of RESORCE and REFLECT trials; and the ongoing Phase III clinical trials. Finally, we discuss how they could address the current problems and possibly reshape the future of the systemic treatments for HCC.